Examining the emotional costs of violations of fidelity beliefs and suspected infidelity among college students. (March 2022) - Weigel, Daniel J.; Shrout, M. Rosie
Abstract: Given that the overwhelming majority of people believe in the importance of faithfulness in romantic relationships, the purpose of this study was to examine the adverse emotional consequences when a partner's suspected infidelity clashes with those beliefs. Applying normative and expectancy violations perspectives, this study examined the connections among subjective norms, infidelity beliefs, and emotional well-being among a sample of 246 university students who suspected their romantic partner of cheating. SEM analyses demonstrated that injunctive and descriptive norms contributed to an individual's beliefs in the importance of fidelity, and when those fidelity beliefs were contradicted by a partner's suspected infidelity, participants experienced greater negative emotion, distress, and depression. The findings deepen the theoretical understanding of suspected infidelity by revealing the direct and indirect connections among subjective norms, fidelity beliefs, and subsequent emotional well-being. Highlights: Individuals have beliefs about maintaining fidelity in relationships. Subjective norms contribute to those infidelity beliefs. A partner's suspected infidelity violates those infidelity beliefs. Violated infidelity beliefs result in emotional distress and turmoil.